Characterization of poly (lactic acid) _ poly (ethylene) glycol blends prepared for melt drawn spinning process - Mohd Akhir, Nur Atiqah; Syed Shaharuddin, Sharifah Imihezri; Buys, Yose Fachmi; Othman, Maizatulnisa; Shaffiar, Norhashimah (Elsevier BV, 2019)
In this study, PLA/PEG blends were prepared using solvent (chloroform) casting methods. PEG was incorporated with increments of 5 wt.% up to 30 wt.% into PLA. Multiple test methods were used to characterize the thermal and structural properties of these blends; Differential Scanning Calorimeter (DSC), Thermogravimetric Analysis (TGA), Fourier Transform Infrared Spectroscopy (FTIR) and optical microscopy (OM). DSC thermograms showed that the incorporation of PEG significantly decreases the glass transition temperature from 55.56°C to 37.35°C and crystallization temperature from 97.14°C to 79°C of the blend. TGA thermograms indicated that the initial and maximum decomposition temperatures for all composition shifted systematically to lower temperature compared to the pure PLA. As the incorporation of PEG into PLA increases, the values of –CH stretching, C=O, C-O wavenumber shifted to lower wavenumber. Lastly, smooth and uniformed fibers were then successfully drawn using an in-house built mini fiber-drawing equipment with an average diameter ranging from 27 to 50 μm.